1990
DOI: 10.1111/j.1439-0418.1990.tb00060.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the importance of nest temperature of Thaumetopoea pityocampa (Den. & Schiff.) (Lep., Thaumetopoeidae)1

Abstract: The thermoeconomy of nests of the 5th instar larvae of Tbaumetopoea pityocampa was studied under laboratory conditions. Measurements over a period of several days showed an up and down in the inner temperature corresponding to the activities of the caterpillars: As the animals left the nest, the temperature inside the nest decreased quickly below than that of the surroundings, which is explained as an effect of transpiration. When the cater illars returned to the nest, the temperature increased to a maximum va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 2 publications
(5 reference statements)
2
18
1
1
Order By: Relevance
“…Larger groups of late stage larvae may enhance the effectiveness of nest web construction (, Tsubaki 1981), and aggregative defense (Itô and Miyashita 1968, Morimoto 1976, , Brown and Cameron 1979, Lawrence 1990). Breuer and Devkota (1990) found that the larval nest of Thaumetopoea pityocampa (Den. and Schiff.…”
Section: Discussionmentioning
confidence: 99%
“…Larger groups of late stage larvae may enhance the effectiveness of nest web construction (, Tsubaki 1981), and aggregative defense (Itô and Miyashita 1968, Morimoto 1976, , Brown and Cameron 1979, Lawrence 1990). Breuer and Devkota (1990) found that the larval nest of Thaumetopoea pityocampa (Den. and Schiff.…”
Section: Discussionmentioning
confidence: 99%
“…Nests are believed to afford protection against predation, parasitism and adverse weather conditions, while improving larval thermoregulation and nest temperatures (e.g. Breuer & Devkota, 1990). Additionally, they may enclose food sources to the advantage of the primary shelter maker, co‐existing organisms and secondary users (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Such a case of social behavior was found by Ruf and Fiedler (2000) in the caterpillars of the insect Eriogaster lanestris (Lepidoptera, Lasiocampidae). The same behavior was found in the tents of the pine processionary caterpillar T. pityocampa (Breuer and Devkota 1990). An increase in ambient temperature, such as the one predicted by global warming scenarios is going to have unpredictable consequences to the survival of the insect and its natural enemies.…”
Section: Insect Extinctions From Climate Changesupporting
confidence: 74%